PERBEDAAN PENGGUNAAN METODE PEMBELAJARAN SAS DAN METODE EJA DENGAN MEDIA BIG BOOK TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS 1 DI SD NEGERI GUGUS MUWARDI - Marwan; Henny Dewi Koeswanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Beginning reading ability is the initial ability that must be possessed by students. Not yet optimizing the ability to read early needs a teaching method with the right learning media so that it is more interesting for students in the activity of the reading process. This study aims to determine the difference between the use of the SAS method and the spelling method on the beginning reading skills of elementary school students. This type of research is a quasi experimental research with posttest only control design. The result of t test of control class and experimental class is 0.002. Due to the significance of 0.002 <0.005, it can be stated that Ho is rejected and Ha is accepted, which means that there is a difference between the SAS learning method and the spelling method on the beginning reading ability of grade I elementary school students with Big book media.